SAMARKAND STATE INSTITUTE OF FOREIGN LANGUAGES FACULTY OF ENGLISH PHILOLOGY AND TRANSLATION STUDIES - Jamalova Nafisa Utkirovna; Nurmamatova Nafosat Alisher qizi; To‘lqinova Bahor To‘lqin qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: The study aims to explore the role and significance of General Pedagogy in the modern educational process, focusing on how its theoretical principles shape instructional design, learning environments, and teacher professionalism. The objective is to evaluate the pedagogical framework as a foundational discipline that integrates philosophy, psychology, and didactics into coherent educational practice. A qualitative analytical method was employed, combining document analysis of pedagogical literature with comparative observation of teaching practices in secondary and higher education institutions. Data were synthesized to identify patterns in pedagogical implementation and conceptual development. The results demonstrate that general pedagogy functions as a guiding structure for all branches of educational science, providing the conceptual base for curriculum design, moral education, and lifelong learning strategies. It was found that institutions applying pedagogical principles consistently achieve higher levels of learner engagement, motivation, and academic performance.
Keywords: Keywords: General Pedagogy; Educational Theory; Teaching Methods; Learning Process; Curriculum Design; Teacher Training; Educational Innovation; Didactics; Student Motivation; Pedagogical Framework; Reflective Practice; Educational Policy.